2004
DOI: 10.1038/nm1081
|View full text |Cite
|
Sign up to set email alerts
|

Effector CD8+ T cells mediate inflammation and airway hyper-responsiveness

Abstract: Allergic asthma is a complex syndrome characterized by airway obstruction, airway inflammation and airway hyper-responsiveness (AHR). Using a mouse model of allergen-induced AHR, we previously demonstrated that CD8-deficient mice develop significantly lower AHR, eosinophilic inflammation and interleukin (IL)-13 levels in bronchoalveolar lavage fluid compared with wild-type mice. These responses were restored by adoptive transfer of antigen-primed CD8(+) T cells. Previously, two distinct populations of antigen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
159
2
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 166 publications
(176 citation statements)
references
References 25 publications
14
159
2
1
Order By: Relevance
“…Our data are in line with recent studies reporting on the effector role of CD8 ϩ T cells in allergic asthma (30,31) and strongly support the idea that the CD4 ϩ Th2 dogma in allergic diseases should be revisited (7). However, although the results presented come from a representative mouse model, studies in humans are required to confirm the hypothesis that CD8 ϩ T cells are involved in the development of AD skin lesions.…”
Section: Discussionsupporting
confidence: 91%
“…Our data are in line with recent studies reporting on the effector role of CD8 ϩ T cells in allergic asthma (30,31) and strongly support the idea that the CD4 ϩ Th2 dogma in allergic diseases should be revisited (7). However, although the results presented come from a representative mouse model, studies in humans are required to confirm the hypothesis that CD8 ϩ T cells are involved in the development of AD skin lesions.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated the presence of CD8ϩ T cells producing IL-4 in bronchoalveolar lavage fluid from patients with SSc, and this finding was correlated with the development of lung fibrosis (23). In addition, CD8ϩ Teff cells were shown to be a source of IL-13 in a mouse model of airway hyperresponsiveness and airway inflammation (46), supporting the idea that CD8ϩ T cells can play important roles in type 2-driven immune responses. Analysis of peripheral blood CD8ϩ T cells indicates that not only is the number of IL-13ϩ Teff cells increased, but the total number of circulating Teff cells in the peripheral blood of SSc patients is also elevated compared with that in normal donors.…”
Section: Discussionmentioning
confidence: 59%
“…In different model systems, CD8 T cell responses are known to require CD4 T cell help and may explain this result (2,18). Interestingly, CD8 T cells have been shown to play a role in airway inflammation and hyperresponsiveness (32,38) and hence their reduced numbers in the lungs may have contributed to the reduction in inflammation we observed. On the other hand, the remaining CD8 T cells might be required for the continued eosinophilic inflammation that we observed in the absence of CD4ϩ cells, and this needs to be investigated in future studies depleting this subset of cells.…”
Section: Discussionmentioning
confidence: 74%